Genetics and genomics of ovarian sex cord‐stromal tumors. Issue 2 (February 2017) - Fuller, P.J.; Leung, D.; Chu, S.
Abstract : Ovarian sex cord‐stromal tumors (SCST) represent approximately 8% of malignant ovarian tumors. The most common are granulosa cell tumors (GCT) which account for approximately 90% of malignant SCST. Recent studies have unraveled the key genomic and genetic events contributing to their pathogenesis. SCST are found in the hereditary syndromes: Peutz‐Jeghers syndrome, Ollier disease and Maffucci syndrome, and DICER1 syndrome. Genomic studies have largely been limited to GCT where a number of recurring chromosomal abnormalities (monsomy and trisomy) have been identified although their contribution to pathogenesis remains unclear. In addition to the recurrent DICER1 mutations reported in non‐hereditary cases of Sertoli cell and Sertoli–Leydig cell tumors, recurrent somatic mutations in both the juvenile (j) and adult (a) forms of GCT have been reported. Approximately 30% of jGCT contain a somatic mutation, the gsp oncogene, while a further 60% have an activating mutation in the AKT gene. In the case of aGCT, a well characterized mutation in the FOXL2 transcription factor (FOXL2 C134W) is found in almost all cases, which arguably defines the disease, although the molecular events that determine the stage, behavior and prognosis of aGCT remain to be determined. Abstract :